2008
DOI: 10.1254/jphs.fp0072346
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Hypolipidemic Effects of a Novel Dual Peroxisome Proliferator-Activated Receptor (PPAR) α/γ Agonist, E3030, in db/db Mice and Beagle Dogs

Abstract: Abstract. We investigated the antidiabetic effects of E3030, which is a potent dual activator of peroxisome proliferator-activated receptor (PPAR) α and PPARγ, in an animal model of diabetes, C57BL / KsJ-db/ db mice (db / db mice), and the lipidemic effects of E3030 in beagle dogs, whose PPARα and PPARγ transactivation responses to E3030 were similar to those of humans. E3030 activated human PPARα, mouse PPARα, dog PPARα, human PPARγ, mouse PPARγ, and dog PPARγ with EC 50 values of 65, 920, 87, 34, 73, and 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The improved metabolic disturbance by triptolide was characterized by decreased levels of Chol, TG and LDL and attenuated obesity. Previous studies showed that high HDL level in db/db diabetic mice [17] was markedly decreased after administration with peroxidase proliferator-activated receptor (PPARα/γ) agonist, rhein, simvastatin or benazepril [16,18,19]. The decreased HDL level was also one of characteristics of improved metabolic disturbance.…”
Section: Discussionmentioning
confidence: 98%
“…The improved metabolic disturbance by triptolide was characterized by decreased levels of Chol, TG and LDL and attenuated obesity. Previous studies showed that high HDL level in db/db diabetic mice [17] was markedly decreased after administration with peroxidase proliferator-activated receptor (PPARα/γ) agonist, rhein, simvastatin or benazepril [16,18,19]. The decreased HDL level was also one of characteristics of improved metabolic disturbance.…”
Section: Discussionmentioning
confidence: 98%
“…29 However, cotreatment with fenofibrate and L-NAME decreased the serum triglyceride levels without altering neovascularization, indicating that the effect of fenofibrate was independent of serum triglyceride level. The chosen dose of fenofibrate has been previously published in mouse studies, 30,31 and no harmful effects were observed in BP, appearance, or body weight. We believe that our study setting is appropriate to estimate the effect of fenofibrate in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Consider the context provided by a difference in cell type, such as a neuron and a blood cell, where a reference set of CPIs for glutamate receptors could rationally receive stronger weighting for the former cell type than the latter type. Experimentalists have been active in trying to find molecules that modulate "twonode" networks, such that ligands intentionally act on a pair of related targets such as for GPCRs, [87,88] subfamilies of related kinases, [89][90][91] multiple subfamilies of kinases, [92,93] and nuclear hormone receptors, [94,95] with most studies seeking to achieve therapeutic effects. A two-target mechanism is quite possibly the limit of rational design; such is distinct from the multi-target results being shown (and predicted).…”
Section: Discussionmentioning
confidence: 99%